Agricultural Households in Mountain Areas in Pre- and Post-accession Slovenia - Bojnec, Štefan; Knific, Kristina (Journal for Geography, 2010)
This paper analyses structural changes in agriculture and agricultural households in the mountainous areas of the Gorenjska region in Slovenia. The focus is on agricultural multifunctional roles, agricultural and agricultural households’ structural changes pre- and post-accession of Slovenia to the European Union (EU) on the basis of datasets obtained by two in-depth surveys from 2001 and 2007. The analyses confirm adjustments of farm households to the use of subsidies and new regulations, and diversification of agricultural households’ incomes. Short-term and long-term strategies of farm households vary depending on farms’ natural factor endowments for agriculture, farm size and structures of farm households, availability of agricultural land and their rental values, diversification of incomes with self-employment and employment outside the farm household.
Keywords: mountainous areas; agricultural structures; income diversification; household strategies; multifunctional development; Gorenjska; Slovenia; European Union